Is Posttraumatic Growth Helpful in Overcoming Mental Health Disorders Due to COVID-19?: The Moderating Effect of Posttraumatic Growth in the Relationship Between COVID-19 and Psychological Health - Se-Ran Park; Sun-Young Im (Frontiers in Psychology, 2021)
The aim of this study was to investigate the effects of restrictions and concerns related to the coronavirus disease 2019 (COVID-19) on depression, anxiety, and committed action, and examine whether posttraumatic growth (PTG) serves as a protective factor for mental health. In particular, this study evaluated the moderating effects of PTG on the changes in levels of anxiety, depression, and committed action according to changes in COVID-19-related restrictions and concerns using a short-term longitudinal design. The Posttraumatic Growth Inventory was administered to 100 adults with significant traumatic experience living in the Republic of Korea, and the participants were asked to complete diary questionnaires on anxiety, depression, committed action, and restrictions and concerns pertaining to COVID-19. The results showed that anxiety and depression decreased, and committed action increased with an increase in PTG. These results highlight a complex relationship between restrictions and concerns related to COVID-19 and psychological health; based on the results, we discussed the positive impact of PTG on psychological health.